Evidence for profit shifting with tax sensitive capital stocks - Simon Loretz; Socrates Mokkas (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper contributes to the literature providing indirect evidence for profit shifting within multinational companies. In contrast to the previous studies we account for the tax responsiveness of the capital stock and analyse the impact of corporate taxes on both pre- and post-tax profitability. Evidence from our large panel dataset of European subsidiaries supports the profit shifting hypothesis. We find that a 10 percentage point decrease in the tax rate increases post-tax profitability by up to 1.1 percentage points. Further, our results suggest that financial profits and losses are particularly responsive to taxes, which indicates that a large part of profit shifting takes places via debt shifting.
Keywords: H25; H87; C23; 330